Role of Treasury Single Account in the Optimization of Public Sector Funds in Nigeria - Otusajo – Ahmad, Oyelola; Yakasai Aminu, Ibrahim; Lateef, Saheed Ademola (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study delves into the Treasury Single Account (TSA) and its role in the optimization of public sector funds in Nigeria. In the quest to obtain accurate data for this research project, primary data was gathered through a well-structured questionnaire designed to elicit responses from participants, thus fulfilling the prerequisites of this study. The population of the study is 80 staff of the Central Bank of Nigeria (CBN) and the Office of Accountant General of the Federation (OAGF). The survey was conducted through the administration of a structured questionnaire. Descriptive statistics and regression analysis were used in the study. The findings of the study revealed that the Treasury Single Account plays a significant role in optimizing public sector funds. The study concluded that TSA is significant in the optimization of public sector funds in Nigeria. For the purpose of efficiently managing and ensuring transparency and accountability in the utilization of public funds, the government of Nigeria ought to strengthen and consolidate on the gains of implementing the TSA system.